A Study the new Multivariate Anova and Ancova Techniques by Existing Statistical Techniques in Biostatistics: Exploring new techniques in multivariate analysis for biostatistics (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Biometrics is a discipline of statistics that involves the use of various computational andscientific approaches to biological research challenges. Biostatisticians collect data on a variety ofvariables in biological and medical research investigations on a regular basis.Multivariate statisticalanalysis concerns in understanding different aims and background of each of the different forms ofmultivariate regression models and how they relate to each other. Any data study including thedescription of the connection between a response variable and one or more explanatory factors hasused regression methods. There exists sufficient literature on applications of Multivariate Statisticaltools in Biostatistics.The research work develops some new multivariate ANOVA and ANCOVAtechniques for biostatistics involving multiple covariates for different classified data with multipleobservations besides the proposed tests for testing sequential contingencies across different groups ofvarious manifold classifications.